Nilai-Nilai Pendidikan dari Al-Qur’an Surat An-Nisa Ayat 29-31 tentang Targhib dan Tarhib - Winda Nurwijayanti; Enoh; Ikin Asikin (UNISBA Press, 2024)
Abstract. This verse explains the command of Allah SWT to stay away from major sins among the sins that are prohibited from doing it, and Allah SWT has promised his servant that if he avoids major sins he will be entered into a glorious place, namely heaven. Targhib values appear in this verse, namely promises accompanied by persuasion and seduction to postpone the mere benefit of delicacy and enjoyment. This study used a descriptive-analytical collection technique, namely the library (library reasearch) by examining in depth various interpretations and books related to the subject matter of the research. The results of the study suggest that the essence of educational values from the Al-Qur'an Surah An-Nisa verse 31 concerning targhib and tarhib is: Allah SWT forbids his servants to commit grave sins and promises enjoyment for his servants. Allah SWT orders his servants to stay away from big sins, namely every sin that Allah threatens with hell fire, wrath, curse and punishment, and Allah SWT promises pleasure to his servant if he stays away from the prohibitions that Allah SWT has given. The targhib values contained in the Al-Qur'an letter An-Nisa verse 31 are, as Muslims must understand and know about what are the commands and prohibitions that Allah SWT has set, such as the prohibition of committing major sins and the obligation to carry out worship and always believe in Allah SWT. Allah SWT has promised His servants who stay away from major sins and will be sent to a noble place, namely heaven. Abstrak. Ayat ini menerangkan tentang perintah Allah Swt untuk menjauhi dosa-dosa besar di antara dosa-dosa yang dilarang mengerjakannya, dan Allah Swt telah menjanjikan kepada hambanya jika menjauhi dosa-dosa besar makan akan dimasukkan ke tempat yang mulia yaitu surga. Munculah nilai-nilai targhib dalam ayat ini yaitu janji yang disertai bujukan dan rayuan untuk menunda kemaslahatan kelezatan dan kenikmatan semata. Penelitian ini menggunakan metode deskriptif-analitis teknik pengumpulan yaitu kepustakaan (library reasearch) dengan mengkaji secara mendalam berbagai tafsir dan buku yang berhubungan dengan pokok masalah penelitian. Hasil penelitian mengemukakan bahwa esensi dari nilai-nilai pendidikan dari Al-Qur’an surat An-Nisa ayat 31 tentang targhib dan tarhib adalah : Allah Swt melarang hambanya untuk melakukan perbuatan dosa besar dan menjanjikan kenikmatan bagi hambanya. Allah Swt memerintahkan hambanya untuk menjauhi dosa-dosa besar, yaitu setiap dosa yang diancam Allah Swt dengan api neraka, kemurkaan, laknat dan adzab, dan Allah Swt menjanjikan kenikmatan kepada hambanya jika menjauhi larangan-larangan yang telah Allah Swt berikan. Nilai-nilai targhib yang terkandung dalam Al-Qur’an surat An-Nisa ayat 31 ialah, sebagai umat muslim harus memahami dan mengetahui tentang apa saja perintah dan larangan yang telah Allah Swt tetapkan, seperti larangan melakukan perbuatan dosa besar dan wajib menjalankan ibadah dan selalu beriman kepada Allah Swt. Allah Swt telah menjanjikan kepada hambanya yang menjauhi perbuatan dosa besar makan akan dimasukkan ke tempat yang mulia yaitu surga.